Development and real time implementation of intelligent holistic power control for stand alone solar photovoltaic generation system. (December 2021) - Roselyn, J. Preetha; Devaraj, D.; Venkatesan, R.; Raj, Ajith; Chandran, C. Pranav
Highlights: Modified L array method without the empirical constant is proposed for detecting the partial shading of PV panels. The system automatically switches to fuzzy logic sweep inclusion algorithm once partial shading is detected which overcomes the problem of getting struck in local optimum point. Implemented in real time setup and hence the algorithms developed can be scaled up to any large-scale PV systems. Abstract: This paper focusses on real-time implementation of an intelligent Holistic Power-Control system which is suitable for uniform, dynamic-irradiance and shaded-conditions for a stand-alone solar-PV system. The model consists of two intelligent Maximum Power Point Tracking(MPPT) control algorithms under different environmental conditions and a novel shading-detection mechanism. A fuzzy logic MPPT system with rule-base developed from real-time solar panel have been implemented. A partial shading detection mechanism based on power loss generated from solar PV array without any sensors is incorporated in the real-time platform. A fuzzy-logic Sweep-Inclusion algorithm is proposed to reach global maximum power point with fast tracking-time under partially-shaded conditions. To test the performance, real-time PV-system with data acquisition using LabVIEW is developed. The standalone solar-PV system is benefitted by the proposed-method by its less tracking-time and more efficiency, accurate partial shading detection through modified power loss scheme and Fuzzy Logic Sweep-Inclusion algorithm for identifying the global-MPPT point.